Tunable narrow-and-sharp defect modes and transmission peak degeneracy in periodic superconducting photonic crystals - Aimei Liu; Han Gao; Yongjun Xiao; Junze Zheng; Quankun Zhang (PLoS ONE, 2026)
The transmittance and the defect mode (DM) are investigated in a one-dimensional superconducting photonic crystal (PC). The structure is composed of periodically stacked SD/DS pairs with a strict central symmetry, where S and D denote superconductor and dielectric layers, respectively. A sharp and narrow DM emerges at the center of the photonic bandgap. Transmission peak degeneracy can be observed by increasing the period number. With this fractal-like behavior, the transmittance is highly sensitive to external stimuli. The DM wavelength λ c linearly blue-shifts with the hydrostatic pressure, and monotonically red-shifts with the temperature. While increasing the incident angle, λ c bule-shifts first smoothly and then sharply. Notably, enhanced tunability is achieved under low pressures, elevated temperatures, and large incidence angles, suggesting superior modulation capabilities. High pressure sensitivity of the DM wavelength, up to 128nm/GPa, is achieved with low deformations. Moreover, the DM maintains near-perfect transmittance unless the temperature is higher than the critical temperature of the superconductor. These findings highlight the potential of such defect-engineered superconducting PCs for high-performance optical sensing applications.